Certification effect of R&D subsidies on debt financing: do institutional forces matter?. (30th March 2021) - Wu, Ruirui; Liu, Zhiying; Chen, Xiafei; Liao, Suqin
Abstract : This study extends the extant literature on the direct outcome additionality of R&D subsidies by investigating whether R&D subsidies can have an indirect certification effect. Based on the panel data of Chinese listed firms, we argue that in emerging economies, such as China, obtaining R&D subsidies can serve as a quality signal of firms' R&D projects to banks, thereby allowing firms to attract more bank loans. Specifically, 1% increase in R&D subsidies can increase firms' access to bank loans by 0.06%. In addition, by using the lens of institutional contingency, we further examine the effect of institutional forces on the signal‐conveying mechanism of R&D subsidies. The results show that firm‐level state ownership weakens the positive signal effect of R&D subsidies, whereas region‐ and industry‐level institutional forces strengthen the positive signal effect. Our study has important implications for policy makers and firms.